If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 = 3 + 7x + -7 Reorder the terms: 6 + 5x = 3 + 7x + -7 Reorder the terms: 6 + 5x = 3 + -7 + 7x Combine like terms: 3 + -7 = -4 6 + 5x = -4 + 7x Solving 6 + 5x = -4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + 5x + -7x = -4 + 7x + -7x Combine like terms: 5x + -7x = -2x 6 + -2x = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -2x = -4 + 0 6 + -2x = -4 Add '-6' to each side of the equation. 6 + -6 + -2x = -4 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = -4 + -6 -2x = -4 + -6 Combine like terms: -4 + -6 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| 4/5-1/4x=3/5 | | (x)=-0.3x^2+75x-2000 | | Z/-8=0.25 | | 9/8/2/3 | | 2/5x-6=-3/5x+5 | | (3x-1)(2x+3)=6x | | X^2=4x^2-3x | | (3x)(3x)=y | | 5/2n=-2/1.6 | | 2s=3 | | (-2m/n^-3)^2 | | 5(2w+1)=25 | | [11(0.7)]-[(2)*0.11]=x | | 5/6(-18) | | 2q=4x+7 | | 3.2=-0.8 | | X/5.2+89.1=47.2 | | -2x^2+4=8x^2-12 | | 6x+1=1/2 | | 6am-8=2+9m-1 | | 1/2n+4=6 | | x/9=-7/16 | | 6x+1=0.5 | | (X-1/X)^2-(77/12)(X-1/x)+10 | | Y-6=5/6(x-(-18)) | | 75+15x=25x | | 5(2x+7)=-9+34 | | 15x^2-44x+32= | | -5x+6=2(6-x) | | x+4+x+4+x-2+x-2=12 | | a+10-2a=-23 | | a/-2-122=246 |